Learning support software - Teaching process for planning and analysis of experiments - da Almeida Santos, Karol [UNESP]; Costa, Antônio Fernando Branco [UNESP]; Neto, Antônio Faria [UNESP] (FapUNIFESP (SciELO), 2020)
Engineering presents as one of its characteristics, the need of investigating systems, in order to obtain the maximum results from these. Design of Experiment is a method that can support this need, but the intrinsic complexity of the method creates barriers to its understanding, and consequently on its use, with statistics being considered one of the most significant agents, therefore it is necessary to use more efficient approaches for teaching this method. The traditional teaching approaches are not enough to favor learning of the essence from Design of Experiment, since its focus is almost entirely on statistics or, when using technological resources, the tool becomes an actor due to the fact of being a complex analysis software, and suitable for use by experts. So, the purpose of this thesis is to propose a software with teaching characteristics, capable of filling this gap, which was called “The Cake”, a metaphor that refers to the total variability from an experiment, and whose portions are taken by the controllable and uncontrollable effects. Thus, this software was developed with the purpose of providing friendly interfaces, which are similar to text books, to facilitate its use and provide interaction with the user, apart from presenting the analyses in a gradual way.
Software de apoio ao processo ensino - Aprendizagem do método planejamento de experimento
Keywords: Design of experiment; Design of experiment software; Statistics; Teaching software